Customs (adab) of governance as depicted in traditional Malay literature - Hamdan, Rahimah; Sujud, Arba’ie (Serials Publications, 2017)
This paper is aimed at describing the customs (adab) pertaining to the Malay rulers as enshrined in the book (kitab), Tajus Salatin (The Crown of Kings), and to compare it with the behaviour of the first ruler of Singapore in the Malay poem (syair), Syair Tenku Perabu. The political instability brought about by the death of Sultan Mahmud Syah in 1812 was exploited by the British to gain influence in southern Malaya, especially to control trade in Singapore. The cunning of the British in interfering with the crisis that erupted over the coronation of the sultan paid off when Sultan Husain Muadzam Syah was installed as the first ruler of Singapore. From the time of the Malay Sultanate of Aceh in the early 17th century, it had been customary for the book (kitab), Tajus Salatin (The Crown of Kings) to be used as a reference by the Malay rulers during their reign. Accordingly, Sultan Husain Muadzam Syah was no exception in using this book (kitab) as the key to his government policies. However, the behaviour of this leader, as illustrated in Syair Tenku Perabu, was inconsistent with Tajus Salatin (The Crown of Kings). By analysing the texts in Tajus Salatin (The Crown of Kings) and Syair Tenku Perabu, this study highlights the customs (adab) that should have been practised by the ruler in his government and further clarifies the reasons for the fall of the Malay government in Singapore for not complying with the concepts of those customs (adab). This study makes an important contribution, especially in promoting the book (kitab), Tajus Salatin (The Crown of Kings) as a literature on constitutionalism that guided the Malay rulers for generations. In conclusion, a leader needs to understand his responsibilities as the ‘Caliph of Allah’ on this earth so that the country that is ruled by him will be blessed and prosperous.